Femme africaine et romanciers africains: mimétisme ou affirmation? (2010)
The stereotyped portrayal of African woman by Francophone African male writers often generates debates. Considering the relevance of this issue to our essay, we will first have a critical look at the texts written by male writers. Second, we will examine the consciousness/coming into writing of Francophone African women writers, to denounce and correct the false image given to the woman. This article will also shed light on the existing disagreement between Western feminists and their African sisters on the historical and socio-cultural context that constitute the focal point around which African feminism otherwise known as third world feminism revolves. To end, we will advocate a possible cooperation between these two feminist blocs -Western and African feminism.